Beyond the color line and the Iron Curtain : reading encounters between Black and Red, 1922-1963 - Baldwin, Kate A. (New Americanists., 2002)
Re-examines the relations between African Americans and the Soviet Union from a more transnational perspective and shows how these relations were crucial in the formation of Black modernism.